Soccer team`s tactical behaviour: Measuring territorial domain - Clemente, F. M.; Couceiro, M. S.; Martins, F. M. L.; Mendes, R. S.; Figueiredo, A. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
New tactical metrics have been introduced in the last years to allow an understanding on the collective behaviour behind the results provided by notational analysis. Thus, the aim of this article was to propose a new application developed on MATLAB to understand the territorial domain of teams during the game based on players` position and using such data analyse sectors with more variability considering the advantage or disadvantage of team players during a single match as proof of concept. As methodological approach, a total of 1508 instants of a 7-a-side soccer game were analysed. The herein proposed MATLAB application allows obtaining the differences between players from Team A and Team B. Moreover, the approximate entropy is used to assess the variability of each of the 12 field sectors. The results show that the sector with higher variability is the central offensive midfield (1.114), closely followed by the central defensive midfield (1.033). A more dynamic rapport of strength within the central sectors may be the explanation for such a higher variability. In conclusion, this study presented a new and effective application to analyse the territorial domain that can be matched with automatic tracking systems to improve their online potential.